ANALISIS PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA WARUNG AYAM PENYET BAROKAH - Syahab, Muhammad Asyari; Yanti, Aprilda (Jurnal Ekonomi Bisnis Digital, 2023)
The development of the culinary business has experienced quite rapid development. The main factor in the development of this culinary business is the support in the form of tourism, which is now starting to gain attention. Apart from this, the culinary business is a choice for entrepreneurs because the uniqueness it brings is able to attract the younger generation to consume it. One of the culinary businesses is Ayam Penyet which is much sought after by the people of Medan. The aim of this research is to analyze the influence of product quality on customer satisfaction at the " Ayam Penyet Barokah" stall in Medan. The type of research used in this writing is descriptive research, using a qualitative approach. Descriptive research is a form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena. These phenomena can be forms, activities, characteristics, changes, relationships, similarities and differences between one phenomenon and another. The implication of this is that a quality brand will create an image of the product itself in the minds of customers and become a basic motivation for customers.